PRAKTIK PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DI INDONESIA (Studi pada Perusahaan yang Terdaftar di BEI) - Rita Yuliana (InFestasi, 2010)
Corporate social responsibility (CSR) is the recent issue in accounting circumtances.  The background of this issue is the willing of the company to be part of their surrounding. The point of this issue, company is participated in developing the wealth of communities surrounding. In fact, the CSR  practices in Indonesia is already done. Their annual report shows the practice of CSR in many aspects. The main idea in this research is about the practice of CSR in Indonesian company.The population of this research are all of company listed in Indonesian Stock Exchange. The method of sampling is purposive sampling. There are 94 companies used as research sample. Descriptive statistic is used as statistical method in this research. The research result shows the rate of participation of the companies to disclose their CSR practice is low. It shows, there are only 116 from 342 companies disclose their CSR practice. The proportion of CSR disclosure in annual report is also too low. Company also choose showing the issue about community development, labor wealth, and surrounding. Those issues are choosen by the company in order to promote the company.